SURVEY OF A FUNCTIONAL STATE OF MASSETER MUSCLES IN EDENTELOUS PATIENTS BASED ON THE DATA OF SURFACE ELECTROMYOGYOPHY STUDIES - V.S. Kuz; V.M. Dvornyk; G.M. Kuz; G.M. Balya; O.S. Shemetov (Ukrainian Medical Stomatological Academy, 2019)
The difficulty of prosthetics and rehabilitation of patients with complete loss of teeth is associated with a burdened psychological and anatomical status. The main reasons for teeth extractions are periodontal tissue diseases, diseases of hard tooth tissues of carious and non-carious origin and traumas. Complete loss of teeth leads to a large number of local and general complications. The masticatory apparatus undergoes a number of functional and morphological changes. It becomes necessary to manufacture complete removable dentures to prevent the occurrence of pathologies in such situations. The effectiveness at this type of dentures depends on compliance with the protocols of their fabrication and the quality of the basic dental materials. Currently, prosthodontists use thermoplastic plastics in the fabrication of complete removable prostheses, more commonly the main group of materials for this constructions are heat-polymerized acrylic resins. Evaluation of the quality of the fabricated complete removable dentures and of the functional state of the masticatory system after prosthetics is determined by their fixation and stabilization, restoration of the patient's appearance and degree of masticatory effectiveness. It can be determined by using of a surface electromyography an objective method for evaluation of the functional state of muscles by recording of their electrical biopotentials. The aim of our study was to study the functional state of the masseter muscles using surface electromyography in edentulous patients, who got dentures made from a thermoplastic base material «Vertex ThermoSense» in the prosthodontics clinic. Material and methods. We used polyamide (nylon) «Vertex ThermoSense», (Netherlands) in this work, for the fabrication of complete removable dentures. We made dentures for 19 elderly and senile patients (60 years and older) with a complete absence of teeth, who retired to the prosthodontics clinic with a goal of manufacturing new complete removable dentures for the upper and lower jaws. Over the past 3-5 years, they have been using complete removable dentures that were made from acrylic resins. Results. Assessing the results of the electromyographic study after 1 year of using of the dentures, it can be concluded that the amplitudes during compression approach the norm and almost four times higher than before prosthetics. A similar pattern as observed with the arbitrary chewing: the amplitudes approach the norm in comparison with the results before prosthetics. As for the coefficient «K», its value decreased in comparison with the results before prosthetics almost twice, which is largely close to the norm. Conclusion. Based on our study of the functional state of the masticatory muscles using surface electromyography in edentelous patients, who got dentures made polyamide thermoplastic material from a «Vertex ThermoSens», we can conclude that of electromyographic studies before prosthetic treatment are significantly different from normal, and after a year of using of dentures are as close as possible to them, which indicates a quiche adaptation to dentures.